Study of Z boson pair production in e+e− interactions at √s = 192–202 GeV - Dova, María Teresa (2001)
The cross section for the production of Z boson pairs is measured using the data collected by the L3 detector at LEP in 1999 in e+e− collisions at centre-of-mass energies ranging from 192 GeV up to 202 GeV. Events in all the visible final states are selected, measuring the cross section of this process. The special case of final states containing b quarks is also investigated. All results are in agreement with the Standard Model predictions.